Research on the connection between relational capital and company performance - Szudrowicz, Izabella (Kapitał relacyjny a wyniki organizacji, 2020)
This paper explored the connection between relational capital and company performance by identifying and systemizing management information from publications placed in the Scopus and Web of Science databases. Key research was carried out for the period from 2010 to 2019. This article should be treated as a result of preliminary research of relational capital and company performance based on the desk research. For this initial step the author decided to use a data compilation in order to confirm the significance of the issue. Based on the collected data, the decision was made to develop the topic through a systematic literature review. This second step was to analyse connection between relational capital and company performance based on publications from the period 2010-2019. By focusing on relational capital and company performance in international publications, the results indicated that the number of papers devoted to relational capital has been growing since 2010. This article is an introduction to the topic and an attempt to explain the point of further work on the link between relational capital and company performance
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 124-143